Kritik Nalar Al-Jabiri dan Implikasinya Terhadap Perkembangan Ekonomi Syariah Modern: Perspektif Trilogi Epistemologi untuk Kemajuan Islam - Fadhil Wafa; Abid Rohmanu (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2025)
Modern Islamic philosopher and commentator Muhammad Abid Al-Jabiri helped advance the study of Quranic interpretation today. His critical thinking of Arabic reason made him famous among academics. Abid Al Jabiri's "revivalism" spirit motivated his criticism. In this case, the concept is related to the revival of Islam and efforts to change society. Abid Al Jabiri considered the current Islamic revival to be unsuccessful or even considered a failure. Based on this, Abid Al Jabiri wrote the next trilogy. This trilogy begins with his concern about the modern Arab discourse that cannot solve the problem of Islamic revival. The inaccuracy of Arabs in handling traditions (turats) is a factor that causes the Islamic revival to fail. Based on the perception of differences, the dialectic of understanding of contemporary Arab backwardness versus the dialectic of modern Western progress, the urgency of the Islamic revival does not depend on the orientation of development or its facts. According to al-Jabiri, formulating "the revival of Islamic civilization" is not easy, even unable to achieve progress, either in scientific planning or proportional utopian vision. After that, Al-Jabiri focused on turats (Islamic traditions), studying them and understanding them objectively to gain new insights. The main goal of Al-Jabiri's thinking on the whole turats is to realize socially transformative knowledge while maintaining the sustainability of the Islamic civilization revival program. This article examines Al-Jabiri's rational critique through the perspective of the bayani, irfani, and burhani epistemological trilogy and its implications for the development of modern Islamic economics. The main focus of this study is how the concept of rational critique can be applied to support the progress of Islam, especially in the context of Islamic economic theory and practice. This study highlights the relevance of Al-Jabiri's approach in formulating a more critical and progressive framework for Islamic economic thinking, while also responding to the challenges of modernization. This article also analyzes the contribution of the epistemological trilogy to strengthening Islamic financial practices in a global context. The research findings show that this integrative approach is not only relevant to the development of Islamic economics but also offers a solid foundation for innovation in facing the dynamics of the modern economy.